MANAGEMENT KEPERAWATAN MENGURANGI RASA HAUS PADA PASIEN DENGAN CHRONIC KIDNEY DISEASE : LITERATURE REVIEW - Fida’ Husain; Ika Silvitasari (Jurnal Ilmiah Kesehatan, 2020)
Background : The inability of CKD patients to manage thirst can lead to overhydration which affects an increase in kidney workload and cause complications thereby reducing quality of life. Literature review needs to be done on various ways to reduce thirst that can be done in CKD patients. Method : Searching for articles was conducted on a population of CKD on HD patients, the outcome was a decrease in the intensity of thirst. Searches were carried out using EBSCO, Sciencedirect, Pubmed, as well as Google Shoolar, restricted articles from 2009-2019 and experimental studies. Results : Interventions carried out to reduce the thirst of CKD patients included chewing ice cubes, chewing gum, and gargling with mouthwash with p value <0.005. Conclusion : All the interventions from the literature review in the form of chewing ice cubes, chewing gum, and gargling with mouthwash can be used to reduce thirst in patients with CKD. Keywords: thirst, CKD, hemodialysis, literature review